The construction of individual criminal culpability 1199-1245: heresy, inquisitio and Inquisition - McManus, Timothy (2020)
During the long twelfth century (ca.1070-ca.1240) medieval society was undergoing a dramatic transformation. Power structures were becoming centralised, bureaucratic and hegemonic, to the exclusion of smaller communities and regional variations. The most important and long-lasting effect of the long twelfth century was the renewed power of the written word. During the long twelfth century, the written word afforded elites the power to coerce and subjugate people in a manner that had previously been denied to them. No better example of this new bureaucratic and authoritative legal construction exists than the Inquisition. The Inquisition, as an institution, relied on the production of written documents, to enforce a legislated conception of what the Catholic community should be. In essence, the contestation of religious practice between orthodoxy and heresy, during the thirteenth century, represents a microcosm of the long twelfth century. The enforcement of a homogenous practice at the behest of elites via bureaucratic means. It is into this narrative of heresy and repression that this thesis inserts itself, trying to shade out a subtler picture of inquisitorial development during the early thirteenth century. This thesis outlines two new elements to our understanding of inquisitorial persecution. Firstly, that the persecution witnessed during the high middle ages conformed to a model of human behaviour, labelled as the behavioural immune system, whose structures and actions highlight a continuity of persecution dating from our shared evolutionary roots. Secondly, that the transformation of the process of inquisitio (the legal mechanism of trial without a named accuser) into Inquisition was centred upon individual criminal culpability and recognition of that within a stringent legal process, which was ultimately a product of Roman jurisprudence within canon law. Chapter one, ‘Disgusting persecution,’ outlines behavioural immune theory and demonstrates how its features conform to reports of persecution during the high middle ages. Special attention is given to Popes Innocent III and Gregory IX because these men were most influential in shaping the early form of inquisitio, especially its use as an anti-heretical tool. Chapter two, ‘Literate Authority,’ examines the rise of Roman jurisprudence in canon law, with particular reference to the (re)discovery of Justinian’s Digest and the formulation of Gratian’s Decretum. It argues that this Romanising influence led ultimately to the rejection of ordeal at the Fourth Lateran (1215), which in turn necessitated the increased use of inquisitio. Chapter three, ‘Corporate theory,’ examines the growing debate amongst canonists towards the end of Innocent III’s pontificate, concerning the appropriateness of corporate liability and punishment, a tension that was finally resolved by accepting that the rights of the criminally culpable individual must be respected in criminal proceedings. Chapter four, ‘Regional Councils,’ contrasts the early process of inquisitio used by Conrad of Marburg and Robert le Bougre to that established by the regional councils of the mid-thirteenth century, especially Tarragona (1242) and Narbonne (1243). It argues that these regional councils formulated a procedure centred upon recognising individual criminal culpability, through both individual trials and punishment. Chapter five, ‘Inquisition in practice,’ examines inquisitorial records in an effort to demonstrate the evolving nature of the process of inquisitio as it transformed itself into Inquisition. The argument is made that the formulation of Inquisition, represents an accepted level of legislative persecution, conforming to the precepts of behavioural immune theory, which in turn was constrained by the emerging canonical consensus of induvial criminal culpability. This thesis concludes that the usual story of Inquisitorial development stemming from heresy and repression in the Languedoc can be significantly enhanced through an exploration of individual criminal culpability. The combination of canon law and behavioural immune theory-led analysis has tried to reposition our understanding of the emerging inquisitorial process, not simply as a repressive tool of new bureaucrats or their elite masters. The Inquisition contained elements of legislative persecution juxtaposed to highly sophisticated procedural steps outlined to afford for defendant the right to a trial.